Performance of stored electrolyzed seawater for disinfection of Pseudomonas aeruginosa - Ferrer, Michelle Joan C. (Animo Repository, 2020)
Electrolysis of seawater has the ability to produce free chlorine (FC), sodium hypochlorite (NaClO), hypochlorous acid (HOCl) and other oxidants which enable it to kill pathogens making it a viable disinfectant. However, the stability of this disinfectant is somewhat unpredictable during storage. This study determined the effects of storage time on the stability of electrolyzed seawater (ESW) in terms of its physicochemical properties, specifically pH, oxidation-reduction potential (ORP), and free chlorine concentration (FCC) for 83 days and evaluated its disinfection performance on Pseudomonas aeruginosa. The effect of dilution in the disinfection was also investigated at ESW to water ratio of 1:0, 1:1, and 3:6. Pre-filtered seawater was electrolyzed at 1.5 A for 20 minutes using platinum-coated titanium mesh electrodes. The ESW was transferred to opaque high-density polyethylene (HDPE) bottles stored at ambient temperature without direct exposure to sunlight. The physicochemical properties of ESW at different storage times were determined, and its disinfection capability against P. aeruginosa was evaluated. This study has made use of two trials for the physicochemical test due to two different batches of seawater were taken. pH was found to increase over time, having a range of 6.32 to 7.705. The ORP and FCC, on the other hand, decreased over time. In accordance with the literature found, the pH ranges show that hypochlorous acid is the main driver of disinfection. Complete disinfection of ESW at 3:6 dilution was observed until 48 days of storage, while the 1:0 dilution was until 83 days and 1:1 dilution was until 51 days. FC decay (k=-0.1449 day-1 and k=-0.0544 day-1) was determined using Chick's Law. Even at different dilution levels, ESW still proved its bactericidal efficacy in this research.